Herbicides Registered for Pine Management in Florida – 2005 Update - Anna Osiecka; Jarek Nowak; Alan Long; Mark Mossler (EDIS, 2005)
This publication presents a list of herbicides registered for forestry use in Florida (Table 1) and provides information on their basic weed control characteristics and silvicultural applications (Table 2). All herbicide active ingredients important in pine management in Florida are included. Others, that are registered in Florida, but are rather marginally used for pine plantations, like 2,4-D, atrazine, dicamba, paraquat, and simazine, are also listed. Since an increasing number of private and public owners manage their forestlands for non-commodity purposes, herbicides that are intended mostly for turf and/or landscape maintenance, but also labeled for forestry, have been included as well. This document is CIR1475, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published in April 2005.